Digital Trust and Purchase Decisions: A Study on Marketplace Consumers in the Era of Society 5.0 - Jamilah, Jamilah (LIMEEMAS: Jurnal Ilmiah Pendidikan, 2026)
This study aims to analyze the influence of digital trust on consumer purchase decisions in the marketplace in the context of Society 5.0. This research is based on the growing interaction in the digital economy, accompanied by various risks, so trust is a key factor in shaping consumer behavior. This study uses a quantitative, survey-based approach with marketplace users who have experience with online transactions. Data were analyzed using the SEM-PLS approach to test the relationships between variables. The study's results show that digital trust has a positive, significant influence on purchasing decisions. The security dimension and reviews/ratings were found to be the dominant factors in shaping consumer trust. In addition, the results also indicate that trust is not only technical, but also formed through digital social interaction between users. In the context of Society 5.0, trust results from the integration of technological systems with the collective user experience. In practical terms, this research provides implications for marketplace players to improve system security and manage customer reviews strategically. Academically, this research extends the study of digital consumer behavior by emphasizing the social dimension in trust formation.